2016
DOI: 10.1021/acs.chemmater.5b04505
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nanoscale Lithium Nickel Manganese Cobalt Oxide (NMC) on the Bacterium Shewanella oneidensis MR-1

Abstract: Nickel manganese cobalt oxide (NMC) comprises a class of lithium intercalation compounds with the composition L x Ni y Mn z Co 1-y-z O 2 (0 < x,y,z < 1). These compounds are of emerging importance in nanoparticle form as cathode materials for lithium-ion batteries used in transportation and consumer electronics. To evaluate the potential environmental impact of release of this material in the environment, we synthesized NMC nanosheets and investigated their interaction with Shewanella oneidensis, a soil and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
159
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(168 citation statements)
references
References 47 publications
9
159
0
Order By: Relevance
“…Samples for SEM images were prepared by spin‐coating (1000 rpm) a dilute methanolic solution of either NMC or LiCoO 2 onto a pristine boron‐doped SiO 2 wafer. For transmission electron microscopy images of NMC and LCO, see Dogangun et al and Hang et al , respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples for SEM images were prepared by spin‐coating (1000 rpm) a dilute methanolic solution of either NMC or LiCoO 2 onto a pristine boron‐doped SiO 2 wafer. For transmission electron microscopy images of NMC and LCO, see Dogangun et al and Hang et al , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Only a few studies have highlighted the toxicological implications and mode of action of these nanoscale complex metal oxides. A prior study of LCO nanosheets and supported lipid bilayers showed that this material had the ability to alter synthetic bilayer compositional symmetry ; in bacteria, toxicity was the result of dissolution of Ni and Co ions . The impact of nanoscale LCO and NMC on multicellular organisms is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…To further characterize the bulk structure, we performed an experimental Raman study and a computational vibrational analysis. The Raman spectrum of bulk LCO in the range 400 -700 cm −1 is shown in Figure 3b surface being predominant as shown by experiments 10,16 and DFT calculations. 29 Moreover, first-principles thermodynamics 13 show that the LCO(001) surface exhibits two distinct ter- In order to build structural models for the surface, two base unit cells were used.…”
Section: Resultsmentioning
confidence: 69%
“…8,9 The prototypical electroactive CMO used in Li-ion batteries is LiCoO 2 (LCO), with production and use projected to increase. 10 With no established economic incentive to recycle LCO-based batteries, 11 they can contribute to electronic waste in landfills. 12 When exposed to different environmental conditions, CMO nanomaterials undergo transformations that are only beginning to be explored, [13][14][15][16][17] and which could have as-yet unknown biological impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Such a scheme was recently applied in the case of binary metal oxide materials, 24,25 where high-throughput experimental works were used to inform hazard and O 2 (NMC) 17 will partially dissolve in aqueous media, releasing transition metals such as Co and Ni to solution. The metals released from these CMOs have shown toxicity effects in Shewanella oneidensis MR-1 bacteria, 10,16 the eukaryotic water flea Daphnia magna, 26 and have also been shown to potentially impact the lipid ordering in model cell membranes. 27,28 The mechanism for the release of metals from NMC has been studied with experimental and density functional theory (DFT) methods.…”
Section: Introductionmentioning
confidence: 99%